To the 80th anniversary of the birthday of Professor Valeriy Arnoldovich Tyagai - Shirshov, Yu. M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
Valery Arnoldovich Tyagai is one of the most talented scientists working at the Institute of Semiconductors of the Academy of Sciences of UkrSSR from 1963 to 1979.